# Algebra/Precalculus

posted by .

How can I verify that f(x)=(x+3)/(x-2)and g(x)=(2x+3)/(x-1)are inverse functions (i.e. show the process)?

Also, how can I solve (g o f)^-1, if f(x)=x+4 and g(x)=2x-5?
Thanks!

## Similar Questions

1. ### Math - Inverse Functions

Find the inverses of the following functions. y = 3(x - 1)^2, x >= 1 Work: x = 3(y - 1)^2 x = 3(y - 1)(y - 1) x = 3(y^2 - y - y + 1) x = 3y^2 - 6y + 3 And now what do I do!?
2. ### CALCULUS

show that f(x) = x^2-1 (x is greater than and equal to 0) and g(x) = root(x-1) (x is greater than and equal to -1) are inverse functions. when i try f(g(x)) = x and g(f(x)) = x to show that the two functions are inverses it doesn't …
3. ### Algebra

Use composition of functions to show that the functions f(x) = 5x + 7 and g(x)= 1/5x-7/5 are inverse functions. That is, carefully show that (fog)(x)= x and (gof)(x)= x.
4. ### math

verify that f and g are inverse functions. f(x) = 5x^2 x>(or equal too)0 g(x)= (x+2/5)^1/2
5. ### Calculus

F(x) = 1-x and g(x) = 1/x These functions have the property that f = f^-1(inverse) and g = g ^-1. That is, the inverse of f is equal to itself and the inverse of g is also equal to itself. Take the composition of each function with …
6. ### math- precalculus

Help please! I can't seem to get x as the answer to prove that they are inverses of each other! Show what f and g are inverse functions algebraically f(x)= x-1/x+5 g(x)= -5x+1/x-1
7. ### College Algebra

verify that the functions of f and g are inverse of each other by showing that f(g(x))=x and g(f(x))=x; f(x)=In(x-1),g(x)=1+e^x
8. ### Precalculus

Verify that the functions f and g, are inverses of each other by showing that f(g(x))=x and g(f(x))=x. f(x)=4-x^3 g(x)=^3ã4-x
9. ### precalculus

verify the functions are inverses of each other by showing that f(g(x)) =x show work. f(x)=6/1-x g(x)= 1- 6/x
10. ### precalculus

Solve the system of equations at the right by the method of substitution. Verify your results by using a graphing utility. x2+y2-4x+6y-5=0, x+y+5=0 answer: x=-y-5 (-y-5)2+y2-4(-y-5)2+6y-5=0 y=√5-5, y=-5-√5 x+√5-5+5=0 x=-√5 …

More Similar Questions